2014
DOI: 10.1063/1.4876619
|View full text |Cite
|
Sign up to set email alerts
|

Observation of multi-scale turbulence and non-local transport in LHD plasmas

Abstract: We have studied two types of spatio-temporal turbulence dynamics in plasmas in the Large Helical Device, based on turbulence measurements with high spatial and temporal resolution. Applying conditional ensemble-averaging to a plasma with Edge-Localized Modes (ELMs), fast radial inward propagation of a micro-scale turbulence front is observed just after ELM event, and the propagation speed is evaluated as ∼100 m/s. A self-organized radial electric field structure is observed in an electrode biasing experiment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 37 publications
1
24
1
Order By: Relevance
“…9(a)-9(c), we have compared these experimental results with a theoretical model. 24,25 Note that we found that the location at which ÀrT i has a local maximum value was seen near the location at which the E r and/or its curvature (E 00 r ) have local peak values rather than that of the E r -shear (E 0 r ). In a previous study, 23 it was shown that the radial electric field jumps to a larger value during an ELM-free H-mode phase, but, simultaneously, the ion temperature gradient changes little.…”
Section: Discussionmentioning
confidence: 93%
“…9(a)-9(c), we have compared these experimental results with a theoretical model. 24,25 Note that we found that the location at which ÀrT i has a local maximum value was seen near the location at which the E r and/or its curvature (E 00 r ) have local peak values rather than that of the E r -shear (E 0 r ). In a previous study, 23 it was shown that the radial electric field jumps to a larger value during an ELM-free H-mode phase, but, simultaneously, the ion temperature gradient changes little.…”
Section: Discussionmentioning
confidence: 93%
“…When biased electrode is installed on the LHD plasma, the strongly localized radial electric field appears. What is striking is that the double peaks of radial electric field are established [24]. In this case, the region where E † r E r > 0 holds appears.…”
Section: Electric Field Shear Vs Electric Field Curvaturementioning
confidence: 87%
“…Experiments have reported the number of about 10 13 [V 2 /m 4 ] [28,29]. For the case of helical plasmas, this value is suppressed by the factor of S −2 owing to the helical-ripple trapped particles, while the width of the peak is independent of S. Considering the fact that the parameter S is in the range of a few 10 [24], the reduction factor is about ∼ 10 −3 times smaller compared to tokamaks. Experiments have reported the value of ∼ 10 9 [V 2 /m 4 ] [24].…”
Section: Steep and Localized Radial Electric Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the edge harmonic oscillation (EHO) mode is significantly observed at 4.1 s < t < 5.1 s. It is reported that the EHO mode enhances the plasma transport through the edge without significantly increasing the thermal transport [12]. In order to fully understand the MHD mode driven plasma transport phenomena in the transition of edge E r plasma [13], it is necessary to identify the magnetic fluctuation with f 2 -5 kHz. Fig.…”
Section: Resultsmentioning
confidence: 99%